Making formwork construction lean - Ko, Chien-Ho; Kuo, Jiun-De (Journal of Civil Engineering and Management, 2015)
Formwork material and payroll are among the greatest costs in building reinforced concrete structures. Therefore, formwork engineering is a key factor affecting project success. Traditional formwork construction entails non-value-adding activities resulting in waste. The objective of this study is to adapt lean manufacturing techniques to formwork engineering in a bid to reduce waste, specifically by developing a lean formwork construction model. In the model, andon is used to establish an on-site quality control culture, allowing form workers to obtain assistance immediately whenever a problem occurs. In addition, formwork operations are pulled through the kanban system to reduce mould inventory and achieve continuous construction flow. A case study is used to validate the applicability of the proposed model. Results show that the proposed model can effectively reduce waste in the formwork construction flow and increase the value of operations, thus providing a new approach to improving formwork engineering.